The Impact of Green Human Resource Management Practices on Organisational Performance - Alegbesogie, Amenaghawon Igbinigiesu (Vilnius University Proceedings, 2023)
GHRM integrates environmentally friendly principles into human resource policies and strategies, positively impacting the environment and organisational outcomes. By adopting GHRM practices, organisations can enhance their reputation, attract and retain top talent, and increase employee engagement. Initiatives such as eco-friendly recruitment processes, training programs on sustainability, and green employee benefits contribute to a positive organisational culture focused on environmental stewardship. Furthermore, GHRM practices promote resource efficiency, waste reduction, and eco-innovation within the organisation. These efforts result in cost savings, improved operational efficiency, and increased competitiveness. GHRM also facilitates compliance with environmental regulations and reduces the risk of legal and reputational damage. Ultimately, the implementation of GHRM practices leads to improved organisational performance by aligning environmental goals with strategic objectives, fostering employee commitment, and gaining a competitive advantage in the marketplace. Embracing sustainable HR practices is essential for organisations seeking long-term success in the context of environmental challenges and changing societal expectations.